PERAN KOMITE CSR DALAM MEMODERASI HUBUNGAN KARAKTERISTIK DEWAN DIREKSI TERHADAP PENGUNGKAPAN LINGKUNGAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2020-2024) - Azza Rosyadi Zarkani; Faisal Faisal (Diponegoro Journal of Accounting, 2026)
This study examines the impact of board of directors’ characteristics-board size, diligence, diversity, and tenure on environmental disclosure, alongside the moderating role of the Corporate Social Responsibility (CSR) Committee. Integrating the Behavioral Theory of the Firm and Upper Echelons Theory, it investigates how internal governance drives sustainability transparency.                    Focusing on manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024, a purposive sample of 48 companies (240 observations) was analyzed. Secondary data from annual reports, sustainability reports, and Bloomberg Terminal were tested using multiple linear regression and Moderated Regression Analysis (MRA) based on GRI 300 standards.                                                                                                                        The findings reveal that board diligence significantly and positively impacts environmental disclosure, while board tenure has a significant negative effect; board size and diversity show no effect. Furthermore, the CSR Committee fails to moderate these relationships, concluding that its establishment in Indonesian manufacturing firms remains largely symbolic (decoupling) for formal regulatory compliance.